Effect of external magnetic field on the coexistence of superconductivity and JT distortion in iron pnictides. (December 2016) - Pradhan, B.; Goi, S.K.; Mishra, R.N.
Abstract: We have presented a theoretical study for the coexistence of superconductivity (SC) and Jahn–Teller (JT) effect with applied magnetic field on iron based high- T c superconductors in s -wave symmetry. The analytic expressions for the temperature dependence of the SC and JT order parameters are derived by Zubarev's technique of double time single particle Green's function method and solved self-consistently. It is observed that in the interplay region, both the gap parameters exhibit very strong dependence of their gap values. The effect of external magnetic field on the gap parameters and the electronic density of states (DOS) is studied. Abstract : Highlights: A Hamiltonian for Fe based SCs with JT and magnetic field effects is proposed. Zubarev's technique of double time Green's functions is used for calculations. The effect of external magnetic field on the SC and JT gaps is studied. The gap values are calculated from the density of state plots. The Zeeman splitting is clearly observed in the gaps.